Customer Relationship Management (CRM) for Medium and Small Enterprises : How to Find the Right Solution for Effectively Connecting with Your Customers. - Specchia, Antonio (Productivity Press, 2022)
Customer Relationship Management (CRM) systems are a growing topic among small and medium-sized enterprises, entrepreneurs, and solopreneurs, and it is completely clear that CRM is a tool that businesses should have in place to manage sales processes. Teams of salespeople must have a system to run their daily activities, and small businesses and solopreneurs must track their marketing effort, a functioning structure for maintaining their contacts with prospects and clients to improve the effectiveness of their sales effort. CRM tools, once only available to large corporations, is now powerful technology for small and medium businesses. Small and medium business are now able to implement CRM solutions under a more cost/effective balance as an alternative to traditional tools like Salesforce, Dynamics or Oracle. The reason for success is mainly the simplicity of the new tools and solutions have been developed for the management of sales processes. This book discusses how implement a CRM from the perspective of the businessperson -- not the IT consultant or the technical staff. It benefits business development, sales management, and sales process control. Small business owners must understand why and how implementing a CRM will create value for the business -- how it will focus on business development, sales management, and how sales leads develop into happy customers. Small business owners must first understand what a CRM systems is, how it works, what are its main functions, and how it serves to manage workflows in the company⁰́₉s sales department. Generally, entrepreneurs struggle to find the time to read and study complex and fully comprehensive books -- This book provides direct operational guidelines to those who need easy-to-read information about how to use CRM effectively. Business professionals must be able to set it up the CRM systems and avoid mistakes and wasting time. This book provides an overview of what can be done with CRM and how it happens to empower business people to find new customers and win their business. This book discusses the logic of the CRM in sales, giving tips and explanations on why and what happens when implemented in a specific way. Essentially, it will give the entrepreneur the know-how behind CRM in sales in general terms, supporting enhanced customer relationships.